Pembentukan Karakter Siswa Sekolah Dasar Melalui Sastra Anak - Anisa Fajriana Oktasari; Ria Kasanova (Departement of Mathematics Education, 2023)
This study seeks to understand the role of children's literature in the character development of elementary school children. Learning children's literature in elementary school has a significant impact on the development of a child's personality. Although children's literature is intended to entertain, it is still educational. Children's attitudes and behavior can be influenced by reading age-appropriate literature. The research technique used is literature review. Data were obtained from various literary sources, including textbooks, scientific articles, and digital libraries. Examining reading sources that are relevant to the study discussed, namely the impact of learning children's literature on the character formation of elementary school students is the data analysis method used. The findings of this study indicate that a teacher must have knowledge of subjects, teaching materials, and learning strategies in order to teach children's literature for character development. Elementary school children will gain an understanding of good and bad, right and wrong, and appropriate and inappropriate through character education contained in literature.